Investing 101 : from stocks and bonds to ETFs and IPOs, an essential primer on building a profitable portfolio - Cagan, Michele (Adams Media, 2016)
This hands-on lesson in investing keeps you engaged as you learn how to build a portfolio and expand your savings.